If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 + x + 1 = 180 Reorder the terms: -7 + 1 + 2x + x = 180 Combine like terms: -7 + 1 = -6 -6 + 2x + x = 180 Combine like terms: 2x + x = 3x -6 + 3x = 180 Solving -6 + 3x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = 180 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 180 + 6 3x = 180 + 6 Combine like terms: 180 + 6 = 186 3x = 186 Divide each side by '3'. x = 62 Simplifying x = 62
| 10=y*20 | | 4b^2-6+10b=0 | | 7+(2x*4)=(x*-18)+2 | | 2t^2+5t+2=2 | | 4x-8=2x-3+3x-5 | | 8([15-y]/7)=-11-5y | | x(2x-4)= | | (x+5)(4x-1)+2(2-8x)(x-5)=0 | | 3x+7x+21=-29 | | (x-5)(4x-1)+2(2-8x)(x-5)=0 | | 4x-8+x=2x-3 | | x(2y-1)= | | 5x+7=3x+5+2x | | 14.7-40*.11= | | 9x-24+24=0 | | 9x-1/2=9 | | 5x+7=3x+5+x | | 3(C+8)=12 | | 5x2y2/xy | | 9x^4-13x+4=0 | | x-9/7=1 | | -16=4+4x | | 8(2-3x)+11=7(3x-2)+10 | | (5+8x)-2x-4= | | 2(-x+8)=-18 | | y-x-2=0 | | 7(3s+9)=279 | | f(4)=2(4)-3 | | y^2=22.5(22.5-y) | | 4(-x+6)=21 | | 6(2l+5)=42 | | (u+1)*8=16 |